Understanding child sexual abuse - Rowan, Edward L. (Understanding health and sickness series., 2006)
The number of confirmed cases of child sexual abuse in the United States rose from 6,000 in 1976 to 113,000 in 1985 and rose again to 300,000 in 2000. Understanding Child Sexual Abuse explores the dynamics, effects, treatment options, and preventive measures available to both the children and the adults involved in child sexual abuse. Chapters provide: Emphasis and guidance on seeking counseling; Pathways for victims to seek renewed, healthy, and productive lives; Options available for rehabilitating abusers; Personality traits common to abusers; Victim responses to the trauma of abuse; Outlin.